A legacy for learning : the Jane and Raphael Bernstein collection - Stomberg, John R.; Stomberg, John R.; Stomberg, John R.; Flamand, Melissa (Hood Museum of Art, Dartmouth, 2021)
"Published to coincide with the exhibition A Legacy for Learning: The Jane and Raphael Bernstein Collection, organized by John R. Stomberg. Exhibition installations were on view at the Hood Museum of Art between April 3, 2021, and February 6, 2022"--